FINTECH DAN KESEJAHTERAAN, UNTUK MENINGKATKAN AKSES KEUANGAN DI PEDESAAN - Fandiyanto, Randika; Indatun, Firdaus Kamil; Wulandari, Dila; Qomariyah, Fariatul; Wahyuni, Sri; Octavia, Sildalina Tri; Syarofah, Huuriyah Alfiatus (Relawan Jurnal Indonesia, 2023)
Fintech platforms have made digital financial services more accessible to rural communities, allowing people to carry out financial transactions safely and quickly. This has improved economic and social well-being in rural areas, reduced dependence on cash, increased financial inclusion, and given rural communities the ability to manage their finances more effectively and reduce the risk of financial instability. To ensure success on Fintech platforms in rural areas, it is important to sustainability which includes education and training on the use of digital financial technology, reliable digital infrastructure, and policy support. Collaboration between government, financial institutions, universities and communities can create an inclusive and sustainable Fintech ecosystem in rural areas, so that it can empower rural communities to achieve their economic and social potential, and is the key to achieving broader prosperity in rural areas.